Exploring the use of activity-based group therapy in increasing self-efficacy and subjective well-being in acute mental health - Bi Xia Ngooi; Su Ren Wong; Janice Dehui Chen; Vanessa Shi Yin Koh (SAGE Publishing, 2022)
Background/Objectives Self-efficacy is a key component in mental health recovery and improvement in well-being. Mental illness is often resultant of environmental stressors, highlighting the importance of coping skills. Occupational therapists commonly utilise activity-based group therapy to encourage use of activities as coping strategies. However, there has been little research concerning these groups and their role in enhancing self-efficacy in behavioural-based coping skills. This study aimed to explore factors that affect behavioural-based coping self-efficacy during activity-based group therapy in an acute mental health ward. It investigates the relationships between (1) behavioural-based coping self-efficacy with overall mental health self-efficacy and (2) mental health self-efficacy and subjective well-being. Methods Immediately after the first group, participants completed a post-group questionnaire. Participation level was also rated. At discharge, the participants were asked to complete the UK Office of National Statistics subjective well-being tool and the Mental Health Self-Efficacy Scale. Descriptive statistics, independent sample t-tests and one-way analysis of variance were done to examine possible covariates and confounders of all outcome variables. General linear models were then conducted. Results Post-group questionnaire reflected moderate-high self-efficacy (M = 6.92, SD = 2.48) and positive well-being with higher happiness scores (M = 7.42, SD = 2.20) and lower anxiety scores (M = 3.79, SD = 2.85). Coping self-efficacy significantly predicted overall mental health self-efficacy ( p = .014), which in turn significantly predicted positive domains of well-being. Conclusions Performing behavioural-based coping strategies in groups can enhance coping self-efficacy and positive well-being, with possible positive influence on mental health self-efficacy and well-being at discharge.